Granulomatosis with polyangiitis - Ahmad, Zubayer; Tuqan, Sadiqa; Nazimuddin, Mirza; Biswas, Rama; Roy, Anindita (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Granulomatosis with polyangiitis is a small and medium vessel vasculitis. It may affect any organ system. Neurological involvement, though less frequent, mostly manifests as peripheral neuropathy. Central nervous system (CNS) involvement as autoimmune cerebritis is rare but may be devastating. We report a patient having CNS involvement in the form of Parkinsonism long before the development of typical upper and lower airway symptoms. Granulomatosis with polyangiitis was diagnosed on the basis of cavitary lung lesions along with epistaxis, granulomatous inflammation from fine needle aspiration (FNAC) of lymph node and high titer of c-ANCA. The patient was commenced on intravenous methylprednisolone followed by mycophenolate mofetil and responded to treatment. Autoimmune cerebritis may present with subacute manifestation of diffuse CNS involvement.